Initial reflections on teaching and learning Mathematics using tablet in Aprison Education Centre - Njurai, Evelyn; Stefansson, Gunnar; ónsdóttir, Anna H. J; Mwenda, Patrick; Obonyo, Mose; Kariuki, Joseph (Strathmore University, 2017)
Paper presented at the 4th Strathmore International Mathematics Conference (SIMC 2017), 19 - 23 June 2017, Strathmore University, Nairobi, Kenya. The reflections reported in this paper involve an intervention using a tablet as a tool for enhancing teaching and learning of mathematics in a prison education centre in Kenya. The tablet is connected wirelessly to a server running the tutor-web mathematics software, installed at the Centre. The first duty of prison staff-teachers is security and then teaching. With these priorities, the teachers sometimes do not attend to their mathematics lessons for hours or days and hence inmate-students miss continued mathematical instructions. To address the challenge, the use of tablet was implemented as a tool to facilitate continued instructions times and subsequent learning. The participants were Form 1 students in the secondary section of the Centre. Findings show that the use of technology did not only facilitate continued learning, but also changed the inmate-students’ negative attitude towards mathematics, motivated them and improved their mathematics performance. Challenges of using the tablet as a tool were noted. In general, the project continues to facilitate achievement of the mission of Kenya Prison Service (KPS) of containment and rehabilitation of offenders, responsive administration of justice, social reintegration and community protection. Future improvements on the project have been suggested. The findings inform the government’s implementation of digital learning of mathematics which is key for the development of the country. Kiriri Women’s University of Science and Technology Nairobi, Kenya University of Iceland, Iceland gstefans@gmail.com; Naivasha Maximum Security Prison Inmates Education Centre, Naivasha, Kenya